Possible involvement of T helper type 2 responses to Toll-like receptor ligands in IgG4-related sclerosing disease - Akitake, Reiko; Watanabe, Tomohiro; Zaima, Chikage; Uza, Norimitsu; Ida, Hiroshi; Tada, Shinsuke; Nishida, Naoshi; Chiba, Tsutomu (Gut, 2010)
We report a case of immunoglobulin G4 (IgG4)-related sclerosing disease involving the pancreas, liver and salivary glands. Massive infiltration of IgG4-expressing plasma cells was seen in the liver and submandibular lymph nodes. Interestingly, accumulation of IgG4-expressing plasma cells was also seen in the colon and terminal ileum. Peripheral blood mononuclear cells (PBMCs) isolated from this patient exhibited enhanced production of IgG4 and interleukin-10 upon stimulation with Toll-like receptor (TLR) ligands as compared with those from a healthy control. In contrast, production of tumour necrosis factor α and interferon γ by PBMCs from this patient was markedly reduced. Since colonic mucosa is always exposed to TLR ligands derived from commensal organisms, the results of immunological studies suggest that enhanced T helper type 2 responses to intestinal microflora may underlie the immunopathogenesis in this patient with IgG4-related sclerosing disease.